Addition of Ca-soap of Sardinella longiceps oil into the ration: 2. Its effect on physical and chemical characteristics of lamb - A Sudarman; M Muttakin; H Nuraini (Jurnal Ilmu Ternak dan Veteriner, 2008)
Lamb contains high saturated fatty acids and cholesterol. Consuming such meat tends to increase atherosclerosis incident. Fat content and composition of meat might be manipulated by giving lemuru fish oil which is rich in HDL and unsaturated fatty acids into sheep diet. Giving lemuru fish oil in the protected form, such as complex calcium-soap is believed to be more beneficial. Twelve sheep were distributed into four groups to receive four experimental diets in studying the influence of calcium soap on meat quality. The sheep were allocated based on Randomized Block Design and at the end of rearing period they were slaughtered. The experimental diets were: R0 = control diet, R1 = R0 + 1.5% calcium soap, R2 = R0 + 3% calcium soap and R3 = R0 + 4.5% calcium soap. Data were analyzed using analysis of variance and any significant differences were further tested using contrast orthogonal. The results showed that the treatments significantly (P<0.01) reduced fat content, both of low density lipoprotein cholesterol (LDL), and high density lipoprotein cholesterol (HDL) of sheep meat. There were no differences in tendernes, cooking loss, water holding capacity (WHC) and pH of meat. It is concluded that the best level of Ca-soap fish oil addition to yield healthy meat is 3%. Key Words: Calcium-Soap, Lamb Meat, Fat, HDL-Cholesterol, LDL-Cholesterol